2017
DOI: 10.1155/2017/1324276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NxTAG Respiratory Pathogen Panel and Comparison with xTAG Respiratory Viral Panel Fast v2 and Film Array Respiratory Panel for Detecting Respiratory Pathogens in Nasopharyngeal Aspirates and Swine/Avian-Origin Influenza A Subtypes in Culture Isolates

Abstract: This study evaluated a new multiplex kit, Luminex NxTAG Respiratory Pathogen Panel, for respiratory pathogens and compared it with xTAG RVP Fast v2 and FilmArray Respiratory Panel using nasopharyngeal aspirate specimens and culture isolates of different swine/avian-origin influenza A subtypes (H2N2, H5N1, H7N9, H5N6, and H9N2). NxTAG RPP gave sensitivity of 95.2%, specificity of 99.6%, PPV of 93.5%, and NPV of 99.7%. NxTAG RPP, xTAG RVP, and FilmArray RP had highly concordant performance among each other for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Our study showed very good agreement between the BioFire FA RP and the Luminex NxTAG RPP for the detection of respiratory pathogens on bronchoscopy specimens. Other studies confirmed high agreement between the FA RP and various versions of the Luminex respiratory panel on NP swabs (Chan et al 2017;Chen et al 2016;Popowitch et al 2013;Tang et al 2016). A few studies, which have included NP swabs and a limited number of BW and BAL, found that FA RP detected more viruses than the Luminex method (Babady et al 2012;Rand et al 2011).…”
Section: Discussionmentioning
confidence: 73%
“…Our study showed very good agreement between the BioFire FA RP and the Luminex NxTAG RPP for the detection of respiratory pathogens on bronchoscopy specimens. Other studies confirmed high agreement between the FA RP and various versions of the Luminex respiratory panel on NP swabs (Chan et al 2017;Chen et al 2016;Popowitch et al 2013;Tang et al 2016). A few studies, which have included NP swabs and a limited number of BW and BAL, found that FA RP detected more viruses than the Luminex method (Babady et al 2012;Rand et al 2011).…”
Section: Discussionmentioning
confidence: 73%
“…6 To detect the presence of 18 respiratory virus targets and four bacteria (including adenovirus, coronaviruses [HCoV-229E, HCoV-Nl63, HCoV-Oc43, HCoV-HKU1, and MERS-CoV], human metapneumovirus, respiratory syncytial virus, human rhinovirus or entero virus, influenza A viruses [H1, H1-2009 and H3], influenza B virus, parainfluenza viruses [types 1 -4], Bordetella pertussis, Bordetella parapertussis, Chlamydophila pneumoniae, and Mycoplasma pneumoniae), samples were tested using BioFire FilmArray Respiratory Panel 2 plus (bioMérieux, Marcy l'Etoile, France) according to the manufacturer's instructions. 7 The two faecal samples were taken from the patients who had diarrhoea as part of their symptoms, and the samples were tested by BioFire FilmArray Gastrointestinal panel (bioMérieux) for 22 diarrhoeal pathogens.…”
Section: Respiratory and Diarrhoeal Pathogen Detectionmentioning
confidence: 99%
“…Saliva specimens were tested for respiratory viruses using NxTAG™ Respiratory Pathogen Panel IVD (Luminex, Austin, TX, USA) as described previously [22,25]. Differentiation of rhinovirus and enterovirus was performed by sequence analysis of the VP4/ VP2 gene region.…”
Section: Study Setting and Designmentioning
confidence: 99%